Kepemimpinan Kepala Desa Milenial dalam Meningkatkan Tata Kelola Desa di Desa BC Kecamatan Trowulan Kabupaten Mojokerto - Lestari, Minar Dita; Lestari, Yuni; Prasetyawan, Agus; Anwar, Muhammad Khairul (ANTASENA: Governance and Innovation Journal, 2026)
Millennial leadership in village government is important because village leaders work directly with citizens, local institutions, and public services. This study aims to describe the application of millennial village head leadership in improving village governance in BC Village, Trowulan District, Mojokerto Regency. This research used a descriptive qualitative approach. Data were collected through observation, semi-structured interviews with 11 informants, and documentation. The results show that the village head applied five characteristics of millennial leadership that support more effective village governance. Digital mindset appeared in the use of digital technology for publication, communication, public services, transparency, and the dissemination of village information. Observer and active listener appeared through direct observation of community conditions, validation of citizen complaints, and open communication. Agile leadership appeared in the ability to respond to changes, utilize external cooperation, and accelerate delayed infrastructure development. Inclusive leadership appeared in village deliberations and the involvement of village institutions and community groups. Brave to be different appeared in work culture reform, BUMDes development, and policy changes. The study concludes that millennial leadership in BC Village works through practical, adaptive, participatory, and change-oriented actions, although it still faces limitations in human resources, digital literacy, passive staff participation in internal meetings, and community resistance to new policies. Furthermore, the leadership practices show tendencies toward servant, democratic, and transformational leadership styles that complement the characteristics of millennial leadership.